Manejo diagnóstico de la artritis gonocócica - Tinoco Abad, Ariana Paulette (Machala : Universidad Técnica de Machala, 2019)
Introduction: Neisseria gonorrhoeae, a sexually transmitted pathogen with great global impact. People who have it have a risk of 0.5 to 3% of developing a disseminated gonococcal infection, which is why it is rare and rarely associated with septic arthritis. It is important due to the increase in incidence at the international level and in older age groups. Objective: To determine the guidelines on the diagnostic management of gonococcal arthritis through the analysis of indexed scientific articles, which allows a correct diagnosis and timely treatment. Methodology: Descriptive study based on the compilation of scientific information in databases such as COCRHANE, PUB-MED, SCIELO, in indexed journals. Conclusions: Regarding its definitive diagnosis, it is performed with the evidence of Neisseria Gonorrhoeae in a non-mucosal site and in the second line, a mucosal test, being of great interest the nucleic acid amplification test (NAAT) that shows great effectiveness for the detection of neisseria. gonorrhoea. Due to the resistance of the gonococcus to penicillin, tetracycline and fluoroquinolone its use has been discontinued, replacing it with combination therapy of ceftriaxone and azithromycin.
Introducción: Neisseria gonorrhoeae, un patógeno de transmisión sexual con gran impacto mundial. Las personas que lo poseen tienen un riesgo del 0.5 al 3% de desarrollar una infección gonocócica diseminada, razón por la cual es poco frecuente y rara vez se asocia con artritis séptica. Es importante debido al aumento de la incidencia a nivel internacional y en grupos de mayor edad. Objetivo: determinar los lineamientos sobre el manejo diagnóstico de la artritis gonocócica mediante el análisis de artículos científicos indexados, que permita un acertado diagnóstico y oportuno tratamiento Metologìa: Estudio descriptivo basado en la recopilación de información científica en bases de datos como COCRHANE, PUB-MED, SCIELO, en revistas indexadas. Conclusiones: En cuanto a su diagnóstico definitivo se realiza con la evidencia de Neisseria Gonorrhoeae en un sitio no mucosal y en segunda línea prueba mucosal siendo de gran interés la prueba de amplificación del ácido nucleico (NAAT) que muestra gran efectividad para la detección de neisseria gonorrhoea .Debido a la resistencia del gonococo a la penicilina, tetraciclina y fluoroquinolona se ha descontinuado su uso, sustituyéndolo por terapia combinada de ceftriaxona y azitromicina.
Keywords: ARTRITIS GONOCOCICA; DIAGNOSTICO; NEISSERIA GONORRHOEAE; ENFERMEDAD GONOCOCICA DISEMINADA